Récupération des gaz torches au démarrage des trains de production au niveau de complexe GL2/Z - KEBAILI Hadj (faculté des sciences et technologie, 2022)
Le présent travail a pour objet l’analyse et la valorisation du gaz naturel et des gaz torchés au niveau des complexes de liquéfaction du gaz naturel d’Arzew (GL2Z). Les analyses du gaz naturel et des gaz torchés ont été réalisées par la technique de chromatographie en phase gazeuse.The present work aims at the analysis and the valorization of natural gas and flared gases at the level of the natural gas liquefaction complexes of Arzew (GL2Z). The analyses of natural gas and flared gases were carried out by the technique of gas chromatography. The analysis of the obtained results shows the necessity to recover these flared gases for two major interests. The development of important quantities of flared gas could constitute on the one hand an economic stake of first order. On the other hand, the rejection in the open air of important quantities of gases such as methane, ethane, propane, n-butane, isobutane, isopentane, n-pentane, C+6 constitutes a pollution factor and contributes to the degradation of the quality of the environment. To this end, we proposed the design of a recovery unit based on the composition of flared gases and the study of the daily situation of the GL2Z complex. The latter is composed of a heat exchanger, a compressor, a cooler using seawater, an exchanger using liquid propane, two Joule Thompson valves, suction tanks and other separation tanks. A sizing study of the various equipment of the recovery unit was carried out according to two methods. It is a classical method and another numerical method based on simulation using software such as HYSYS.
Keywords: Récupération des gaz; torches au démarrage des trains; production au niveau de complexe GL2/Z;GL2/Z